How well do building energy performance certificates predict heat loss? - Tensay Hadush Meles; Niall Farrell; John A. Curtis (The Economic and Social Research Institute (ESRI), 2022)
This paper evaluates the predictive power of building energy performance certificates on ex-post home heat loss. Improving the insulative capacity of residential properties is a policy priority in many markets, with building energy performance certificates providing the indicative benchmark. We exploit a rich panel dataset of high-frequency thermostat readings, coupled with data detailing weather and buildings characteristics, to identify an ex-post metric of heat loss. Our results show a significant effect of building energy performance rating on indoor temperature, a proxy for home heat loss. However, we do not find evidence of a distinct gradient in performance between building energy rating categories, as suggested by ex-ante estimates of home heat loss.
Keywords: C55; D12; Q4; Q55; 330; Energy-efficiency; Energy performance gap; Home heating; High-frequency data; Smart thermostat